2019
DOI: 10.1002/jper.19-0290
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of growth factors in advanced platelet‐rich fibrin and concentrated growth factors and their clinical efficacy as adjunctive to the GTR procedure in periodontal intrabony defects

Abstract: Background:The development of platelet concentrated biomaterials has gained increasing awareness for regenerative medicine. With different protocol, derivatives such as advanced platelet-rich fibrin (A-PRF), injected platelet-rich fibrin, and concentrated growth factor (CGF) have been demonstrated effectively in preclinical and clinical studies. The aim of this study was to compare the level of growth factors releasing from A-PRF and CGF, and their clinical efficacy in the regenerative management of intrabony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
75
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 39 publications
5
75
0
1
Order By: Relevance
“…This hyper-concentrated growth factors media may result in a cytotoxic environment under in vitro conditions. This hypothesis is in agreement with previous reports that highlight the role of the fibrin network in the release kinetics of growth factors [3,45,46].…”
Section: Discussionsupporting
confidence: 94%
“…This hyper-concentrated growth factors media may result in a cytotoxic environment under in vitro conditions. This hypothesis is in agreement with previous reports that highlight the role of the fibrin network in the release kinetics of growth factors [3,45,46].…”
Section: Discussionsupporting
confidence: 94%
“…We believe, therefore, that the growth factors in CGF could stimulate the proliferation of mesenchymal cells, but they do not have the ability to differentiate undifferentiated mesenchymal cells into osteoblasts or chondroblasts. The histological findings were consistent with the report that the concentration of BMP-2 in CGF was fairly low and almost undetectable by ELISA [ 29 ]. The addition of 1.0 µg of rhBMP-2 to the CGF membrane (5 × 5 × 2 mm 3 ) might provide synergistic effects with several growth factors in CGF for bone and cartilage induction.…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, with excluding case series (without a control group), 18 studies on bone regeneration and six studies on regeneration of other tissues are listed in Tables and . Two articles were randomized clinical trials and one was a cohort study in which the treated pathologies were peri‐implantitis, guided tissue regeneration (GTR), and gingival recessions (Bozkurt Dogan et al, ; Isler et al, ; Lei et al, ). Most studies stated improvement of tissue healing or regeneration in the presence of CGF, yet three studies investigating its effect on peri‐implantitis, implant stability, and immediate implants reported no significant difference or lower effect of CGF (Isler et al, ; Özveri Koyuncu, İçpınar Çelik, et al, ; Yang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Combination of CGF with stem cells or grafts resulted in better results than CGF alone (Chen et al, ; Durmuslar et al, ; Honda et al, ; Kizilaslan et al, ; Qiao et al, ; Wang et al, ). Three studies compared CGF to other platelets concentrates; one study reported no significant difference between CGF, PRP, and PRF on bone formation in rabbit‐skull defect (Kim et al, ), another study also confirmed no significant difference in GTR between A‐PRF and CGF (Lei et al, ); while Park et al indicated better bone formation of CGF than PRF in femur defect of adult dogs (Park et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation